The use of videofluoroscopy (VFS) and fibreoptic endoscopic evaluation of swallowing (FEES) in the investigation of oropharyngeal dysphagia in stroke patients: A narrative review. Issue 2 (March 2023) - Helliwell, K.; Hughes, V.J.; Bennion, C.M.; Manning-Stanley, A.
Abstract: Objectives: Patients with suspected acute stroke require rapid assessment of swallowing on admission. If aspiration is suspected, this takes the form of specialist assessment, using either videofluoroscopy (VFS) or fibreoptic endoscopic evaluation of swallowing (FEES). The review aim was to evaluate and compare the effectiveness of each method in stroke patients. Literature was collected from the databases Scopus, Web of Science and Medline, and articles included in the review were published within the last 10 years, in the English language. Key findings: Sensitivity and specificity ranged from 0.29–0.33 and 0.96–1.0 for VFS, respectively, and 0.37–1.0 and 0.65–0.87 for FEES, respectively, depending on the type of bolus utilised. VFS is the current gold-standard for the investigation of oropharyngeal dysphagia (OD), however, radiation dose and patient transport implications mean FEES may be preferred. FEES has limitations including 'whiteout' and the invasive nature of the endoscope. The NICE guidelines do not recommend a definitive protocol specifically in stroke patients. This suggests further research may be required to determine the most effective method. Conclusion: FEES is a beneficial first line examination, providing limited invasiveness, and administering a high level of patient suitability, without using ionising radiation. VFS could potentially be useful following FEES to secure full visualisation, ensuring an aspiration event is not missed during FEES. Implications for practice: Use of FEES as the first line test rather than VFS, ensures radiation dose is as low as reasonably practicable (ALARP). Ongoing research to ensure protocols follow current best practice can help ensure accurate management of oropharyngeal dysphagia in stroke patients.